Pengaruh Optimisme dan Dukungan Sosial terhadap Problem Focused Coping pada Mahasiswa Fakultas Ushuluddin, Adab, dan Dakwah UIN Sayyid Ali Rahmatullah Tulungagung yang Sedang Menyusun Skripsi - Moh. Torikul Anwar; Mirna Wahyu Agustina (Faculty of Ushuluddin and Humanities, 2022)
This study of aims to see the effect of optimism and social support on problem focused coping on students of the Ushuluddin, Adab dan Dakwah UIN Sayyid Ali Rahmatuklah Tulungagung students who are writing thesis. This research method is using quantitative methods. The subjects to 90 final students, the sampling technique and data collection techniques using ascale, data processing using multiple rergression analysis. The result obtained in the partial t test, the significant value of the optimism variable is 0.000<0.05 and the social support variable is 0.03<0.05. simultaneously optimism and social support with a significant value of 0.000<0.05 and F count 53.452>F table 3.10. Therefore, it can be said that there is a simultasneous effect of optimism and social support on problems that focus on coping on students who are working on their thesis.